Asking Bing with GPT-4 about the Antibiotic Use of Clays - Carlos Alves (Medical Sciences Forum)
In this work, Microsoft Bing chat with GPT-4 was used for researching the antibiotic use of clays by submitting three requests that were literally the following: (+) write a bullet list of the most important points concerning research on the use of clay minerals for preparing antibiotics; (+) write a bullet list of suggestions for future and original research, not performed before, on the use of clay minerals for preparing antibiotics; (+) write a bullet list of the most important results of clinical trials of clay minerals as antibiotics. Bing’s answers were extensive, containing information on mineralogical and health issues. Bing also suggested follow-up questions, some of which were also included, and that expanded the topics considered to domains of ethics and arguably even politics, with repeated references to “respecting the traditional knowledge and practices of indigenous or local communities that have used clay minerals for medicinal purposes for centuries”, including the answer to the following question suggested by Bing, “How can we improve the antibiotic activity and specificity of clay minerals?”.